Degradation of emerging organic pollutants in wastewater effluents by electrochemical photocatalysis on nanostructured TiO2 meshes. (1st November 2019) - Murgolo, S.; Franz, S.; Arab, H.; Bestetti, M.; Falletta, E.; Mascolo, G.
Abstract: An immobilized photoactive TiO2 coating grown directly on titanium meshes was successfully exploited for the electrochemical photocatalytic degradation of carbamazepine in real secondary wastewater effluent. The catalyst was prepared by Plasma Electrolytic Oxidation and during the photocatalytic water treatment an electrical polarization (bias) was applied to the catalyst. The investigated process was compared with the conventional one employing suspended TiO2 powder (Degussa P25). Results showed that carbamazepine degradation rate follows the order UV/supported TiO2 +bias ≈ UV/TiO2 Degussa P25 > UV/supported TiO2  > UV. The investigation also included the identification of other micropollutants and degradation products. This allowed the detection of 201 compounds present in the secondary wastewater effluent employed for the photocatalysis tests, 51 of them also successfully associated to compounds of emerging concern (CECs), and 194 to transformation products (TPs). The degradation of detected compounds followed first-order kinetics and the mean kinetic constant values of the 51 CECs resulted to be 0.048, 0.035 and 0.043 min −1 for the TiO2 +Bias + UV, TiO2 +UV and UV, respectively. As for TPs, results showed that the TiO2 +Bias + UV treatment is much more efficient than both TiO2 +UV and UV in minimizing the intensity of the organics in the real wastewater. Such a better performance was more pronounced at higher reaction time reaching 60% reduction of mean peak area of TPs at 90 min of reaction. Among the detected TPs also compounds belonging to known carbamazepine TPs were found. This allowed to propose a degradation pathway of carbamazepine. The supported catalyst was positively tested for 15 cycles demonstrating that it has the potential to be used in real wastewater tertiary steps aimed at removing CECs. Highlights: Immobilized TiO2 on titanium mesh was used for CECs photocatalysis in wastewater. Over 200 organic compounds present in secondary wastewater effluent were removed. The supported catalyst was positively tested for 15 cycles. The electrophotocatalityc process can be used for removing CECs in real wastewater.